ERSEPSI SISWA TERHADAP PENGGUNAAN MEDIA PEMBELAJARAN GOOGLE CLASSROOM DALAM PEMBELAJARAN DARING PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 BANTUL - Maryati Maryati; Natalina Premastuti Brataningrum (Universitas Sanata Dharma, 2021)
The purpose of this research is to know students’ perception of the use of google classroom as a medium of online learning in economic subject at SMA Negeri 3 Bantul. This kind of research was descriptive with quantitative research. The population in this research are all the students majoring in social studies at SMA Negeri 3 Bantul, which consisted of 281 students. The samples in this research were 165 students who were taken by convenience sampling. Data were collected by questionnaires and interviews and analyzed by descriptive analysis.The results in this research showed that: (1) Students’ perception of the use of google classroom as a medium of online learning in economic subject at SMA Negeri 3 Bantul were positive with a tendency rate of 43. (2) student learning outcomes while using the google classroom learning media are included in the high category with a tendency rate of 77%.Keywords : Perception, google classroom and online learning